2018
DOI: 10.1080/21548331.2018.1535977
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of glycemic control among diabetes mellitus patients in a tertiary clinic in Gaborone, Botswana: findings and implications

Abstract: Background and aims: Glycemic control among patients with diabetes mellitus is associated with a marked reduction of both macrovascular and microvascular complications; however, glycemic control remains an elusive goal worldwide. The aim of this study was to determine factors associated with glycemic control among patients attending a tertiary clinic in Botswana as limited information to date. Methods: Cross-sectional study in a tertiary clinic in Gaborone, Botswana. Patients were recruited between 21 st July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…FDCs have been developed to reduce the pill burden as well as potentially enhance adherence and outcomes in patients with T2DM [46,[210][211][212], with reduced pill burden along with improved effectiveness and reduced side-effects welcomed by patients [213]. Poor control of patients with T2DM is a concern especially among African countries [162,[214][215][216][217].…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%
“…FDCs have been developed to reduce the pill burden as well as potentially enhance adherence and outcomes in patients with T2DM [46,[210][211][212], with reduced pill burden along with improved effectiveness and reduced side-effects welcomed by patients [213]. Poor control of patients with T2DM is a concern especially among African countries [162,[214][215][216][217].…”
Section: Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%
“…This includes addressing sub-optimal management of patients with T2DM with currently only a minority of patients in SSA achieving glycemic control (Mwita et al, 2012;Sobngwi et al, 2012;Kibirige et al, 2014;Pinchevsky et al, 2015;Manne-Goehler et al, 2019). Glycemic control is improved though in specialist centers in SSA (Sobngwi et al, 2012;Mwita et al, 2019;Rwegerera et al, 2019). This reflects the fact that NCDs such as diabetes have been relatively neglected over the last decade across Africa in favor of infectious diseases including human immunodeficiency viruses (HIV), tuberculosis (TB), and malaria due to their burden (Atun et al, 2017;Pastakia et al, 2017;South African Lancet National Commission, 2019).…”
mentioning
confidence: 99%
“…Treatment, including adherence to agreed guidelines for patients with T2DM, and subsequent patient adherence to prescribed medicines, are also generally sub-optimal in LMICs including Africa (Igbojiaku et al, 2013;Awodele and Osuolale, 2015;Fadare et al, 2015;Moosa et al, 2015;Sapkota et al, 2015;Elsous et al, 2017;Abate, 2019;Moosa et al, 2019). A number of factors appear responsible for poor control of T2DM including the age of patients, their lack of perception of the consequences of diabetes, forgetfulness regarding taking medication, adverse effects of the prescribed medicines, living in rural areas, affordability, and issues of motivation including family support (Adegbola et al, 2016;Abate, 2019;Dedefo et al, 2019;Mwita et al, 2019;Rwegerera et al, 2019). There are also concerns with the c o n c o m i t a n t m a n a g e m e n t o f h y p e r t e n s i o n a n d hypercholesterolemia along with controlling HbA1c in patients with T2DM in Africa (Gudina et al, 2011;Sobngwi et al, 2012;Mwita et al, 2019).…”
mentioning
confidence: 99%
“…Five studies assessed the relationship between increasing age and glycaemic control [27,31,34,58,61], two found that it was negatively associated with glycosylated haemoglobin [31,61], and one that it was associated with good glycaemic control [58]. Older age was associated with poor glycaemic control in twelve studies [22,29,32,36,39,65,68,69,73,77,83,86]. Eight studies assessed the relationship between the female gender and glycaemic control [18,29,34,51,61,64,65,73], two studies found that the female gender was associated signi cantly with poor glycaemic control [18,34] versus one study that linked it to good glycaemic control [29].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Older age was associated with poor glycaemic control in twelve studies [22,29,32,36,39,65,68,69,73,77,83,86]. Eight studies assessed the relationship between the female gender and glycaemic control [18,29,34,51,61,64,65,73], two studies found that the female gender was associated signi cantly with poor glycaemic control [18,34] versus one study that linked it to good glycaemic control [29]. Male gender in respect of glycaemic control was assessed by eleven studies [27,31,39,44,58,66,75,77,83,85,87], two studies associated it with good glycaemic control [58,75], while two studies linked it to poor glycaemic control [27,87].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%